Innovative biomass cooking approaches for sub-Saharan Africa - Njenga, M.; Gitau, K. J.; Iiyama, Miyuki; Jamnadass, Ramni H.; Mahmoud, Y.; Karanja, N. (African Journal of Food, Agriculture, Nutrition and Development, 2019)
Eradicating poverty and achieving food and nutrition security in a sustainable environment is difficult to achieve without adequate access to affordable cooking fuel. It is therefore important to understand the common sources of cooking energy used by people in rural areas and the challenges faced in making fuel sources economically viable, socially acceptable and ecologically sustainable. In the sub-Saharan Africa (SSA) region, more than 90% of the population relies on firewood and charcoal (wood fuel, collectively) as a primary source of domestic energy. Wood fuel sustainability is challenged by unsustainable harvesting and inefficient methods of converting wood into energy. The use of inefficient cook stoves contributes to wood wastage and smoke exposure associated with severe illnesses. Households often abandon traditional nutritious diets that take a long time to cook, reduce the number of meals, and spend income on fuel at the expense of food costs. Innovations exist that have the potential to provide affordable and cleaner tree-based cooking fuel. Pruning trees on the farm as a fuel source brings firewood closer to women, lightens their workload, saves time and reduces income spent on cooking fuel. Using briquettes or gas cook stoves can reduce health risks associated with food preparation and reduce income spent on cooking fuel due to increased fuel efficiency. The development of these innovations indicates the need for a multi-disciplinary approach to increase awareness of the benefits of cooking fuel innovations, encourage further research on product quality enhancement and standardization, to understand cultural and behavioral issues influencing adoption, and integrate innovations into bioenergy policy frameworks.